Care Model in Health Services with Individual Dual Diagnosis: Misuse of Drugs and Mental Disorders in Indonesia - Mardha Raya; Herni Susanti; Ice Yulia Wardani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Dual diagnosis is a condition of individuals with a history of drug abuse and psychiatric disorders that occur together. The prevalence of dual diagnosis from year to year has increased significantly and has physical, psychological and social impacts that need to be addressed. The purpose of writing this article is to describe the model of care in individual health services with dual diagnosis so far in Indonesia and as an additional literature on dual diagnosis. This article is one of the results of an analysis in a study conducted in April-July 2020, using a qualitative descriptive method with in-depth interviews via online interviews conducted on 8 participants. Data analysis using thematic analysis. The treatment model consists of; 1)integrated care model for dual diagnosis individuals in the realm of hospitalization. 2)phased care model for dual diagnosis individuals in the